Curriculum culture of non-governmental schools (an ethnographic study) - et. al., Fatemeh Mardan Arbat, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The present study aimed to identify the culture of non-governmental school curricula. This goal was achieved through the active presence of the researcher in the study community. This study was conducted in two non-governmental primary schools in Tabriz within the framework of a qualitative approach. The educational ethnography method was used to conduct this study. Also, the required data was through field observations and semi-structured interviews. The thematic content analysis method was used to analyze the said interviews and observations. Components of non-governmental school curriculum culture were categorized as follows: goals, logic and the reason behind the curricula culture of non-governmental schools, valuable content and educational materials used in non-governmental schools, teaching and learning strategies and teachers' role in non-governmental schools, time and space of activities, and school-family relationships. According to the research findings, there was a tendency towards consumerism and materialism in the curriculum culture of non-governmental schools. Also, the purpose of the implementation of the curriculum was to enhance scientific competition and provide families with a choice regarding their children's education.